Psychiatric dictionary. - Campbell, Robert Jean (New York : Oxford University Press, 1989)
Comprehensive dictionary of the vocabulary of psychiatry and allied fields. Incorporates terminology of DSM-III-R. Also includes eponyms, acronyms, and biographical entries. Contains important terms and concepts from the past to the present. Entries include explanatory definitions, references, and dates. Many cross references.
Includes bibliographical references (p. [xiii]).
Keywords: Psychiatry